Comparison of the possible uses and performance analysis of databases on mobile operating systems Mateusz Grudzień*, Konrad Korgol*, Dariusz Gutek - Grudzień, Mateusz; Korgol, Konrad; Gutek, Dariusz (Journal of Computer Sciences Institute, 2016)
This publication presents chosen forms of data persistence such as: Local Storage, Shared Preferences, flat files and SQLite in the context of two widely used mobile operating systems – Android and Windows Mobile. It also describes ways to connect to external database engines such as Microsoft SQL Server, PostgreSQL or MySQL and tries to answer the question which one of these data persistence forms makes the most sense and when. The arguments are based on performance tests that all of the described solutions were participants of.